Analisis Determinan Non – Performing Loan (NPL) Pada Perbankan Di Indonesia - Naura Zahwa; Idris (Media Riset Ekonomi Pembangunan (MedREP), 2026)
This study scrutinizes the determinants of Non-Performing Loan (NPL) ratio within conventional banking institutions in Indonesia over the interval spanning from the first quarter of 2012 to the second quarter of 2025. The inquiry investigates both bank specific constituents, namely the Capital Adequacy Ratio (CAR), a proxy for profitability (Return on Assets/ROA), and the Loan to Deposit Ratio (LDR), alongside macroeconomic externalities, including economic growth (GDP), Inflation (CPI), and lending interest rates. Employing quarterly time series data, the Autoregressive Distributed Lag (ARDL) model is utilized to delineate short - term fluctuations and ascertain long-run cointegration. The bound test substantiates a robust cointegrating relationship among the variables, evidenced by an F-Statistic of 15.421, which exceeds the upper bound critical threshold at the 1% significance level. Estimation outcomes reveal that ROA emerges as the most dominant determinant, exerting a negative and significant influence, a finding consistent with the Bad Management Hypothesis. Conversely, CAR and lending rates demonstrate a positive and significant impact, aligning with Agency Theory and Credit Cycles Theory. Economic growth exhibits a negative and significant effect, thereby corroborating the Procyclicality Theory. Meanwhile, LDR and Inflation are found to exert no significant influence over the long term. The error Correction Model indicates a highly stable adjustment mechanism, with an exceptionally rapid speed of convergence amounting to 90.09% per quarter. These findings imply that sustaining bank profitability and implementing prudent lending rate policies are imperative for controlling NPLs. Consequently, regulatory authorities ought to monitor not only the adequacy of capital but also the behavior tendencies of banks in deploying their excess capital.